2006
DOI: 10.1128/aem.00472-06
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Sampling System for Recovery and Detection of Airborne Porcine Reproductive and Respiratory Syndrome Virus and Swine Influenza Virus

Abstract: The objective of this research was to optimize sampling parameters for increased recovery and detection of airborne porcine reproductive and respiratory syndrome virus (PRRSV) and swine influenza virus (SIV). Collection media containing antifoams, activated carbons, protectants, and ethylene glycol were evaluated for direct effects on factors impacting the detection of PRRSV and SIV, including virus infectivity, viability of continuous cell lines used for the isolation of these viruses, and performance of reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 39 publications
(28 reference statements)
0
74
0
Order By: Relevance
“…Previous research showed that Antifoam A Emulsion was non-virucidal for PRRSV [19]. The nebulizer was operated for 3 min on compressed air (Sears Roebuck, 00916734000, Hoffman Estates, IL, USA) at 40 P.S.I.…”
Section: Aerosolization Of Prrsvmentioning
confidence: 99%
“…Previous research showed that Antifoam A Emulsion was non-virucidal for PRRSV [19]. The nebulizer was operated for 3 min on compressed air (Sears Roebuck, 00916734000, Hoffman Estates, IL, USA) at 40 P.S.I.…”
Section: Aerosolization Of Prrsvmentioning
confidence: 99%
“…After sampling the medium can be concentrated or directly decontaminated, purified, and analyzed. The recovery efficiency of this method is high because it avoids dehydration but flow rate and the composition of the collection fluid are again critical for virus recovery (Hogan et al 2005;Hermann et al 2006).…”
Section: Impinger Samplersmentioning
confidence: 99%
“…We used a similar equipment designed by Hermann to test the recovery efficiency of air virus [15]. A 20 liter glass reservoir was modified to allow simultaneous sample collection at outlet ports.…”
Section: Samplers and Sampling Methodsmentioning
confidence: 99%